Severe Case of Chronic Pelvic Pain Syndrome: Recovery after Injection of Procaine into the Vesicoprostatic Plexus—Case Report and Discussion of Pathophysiology and Mechanisms of Action - R. M. Kronenberg; S. M. Ludin; L. Fischer (Case Reports in Urology)
We describe a patient with a 35-year history of a severe chronic pelvic pain syndrome (CPPS) that failed to adequately respond to various drug therapies and other treatments by different specialists. In addition to the ongoing chronic pain, he suffered from week-long episodes of increased pain with no discernible trigger. At the first consultation with us the patient was in a particularly severe pain phase. He was taking four different analgesically effective drugs. In terms of therapeutic local anesthesia (neural therapy), we performed suprapubic injection of procaine 1% with infiltration of the vesicoprostatic plexus. Just a few minutes later, the pain decreased significantly. To maintain and further increase the effect, we performed the injection six more times. The patient gradually reduced and stopped all drugs and remained free of pain and discomfort ever since. This is the first report of a successful therapeutic infiltration of the vesicoprostatic plexus using a local anesthetic (LA) in a patient with CPPS that has been refractory to different treatments for many years. A possible explanation may be that the positive feedback loops maintaining pain and neurogenic inflammation are disrupted by LA infiltration. This can lead to a new organisation (self-organisation) of the pain-processing systems.